2021
DOI: 10.1016/j.jiph.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

What were the changes during the COVID-19 pandemic era concerning occupational risks among health care workers?

Abstract: Background Accidental exposure to percutaneous needle stick and sharp injuries (NSSIs) and blood and other body fluids is the unintended contact with risky medical instruments or patient secretions during a medical intervention. During the COVID-19 pandemic, the significance of occupational injuries in healthcare professionals was revealed once again. To assess the occupational injuries, we compared rates, distribution and type of exposure to blood and body fluids and NSSIs of health care workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The coronavirus disease 2019 (COVID-19) pandemic has been identified as a public health concern globally, threatening individuals’ physical and mental health ( Fiorillo & Gorwood, 2020 ; Kumar & Nayar, 2021 ). Serving as crisis management personnel, medical staff are exposed to a high range of occupational risks whose severity and likelihood have increased since the pandemic outbreak (Blanco-Donoso et al, 2020; Diktas et al, 2021 ; El‐Boghdadly et al, 2020; Franklin & Gkiouleka, 2021 ; Veziant et al, 2020). Several well-documented risk factors faced by the medical staff in the workplace during COVID-19 include high workload, direct contact with infected individuals, facing a higher rate of moral dilemmas (e.g., taking decisions about life and death), limited collegial and managerial support, perceived helplessness due to lack of experience or equipment and prolonged separation from families ( Gohar et al, 2020 ; Fang et al, 2021 ; Shanafelt et al, 2020 ; Walton & Christian, 2020; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic has been identified as a public health concern globally, threatening individuals’ physical and mental health ( Fiorillo & Gorwood, 2020 ; Kumar & Nayar, 2021 ). Serving as crisis management personnel, medical staff are exposed to a high range of occupational risks whose severity and likelihood have increased since the pandemic outbreak (Blanco-Donoso et al, 2020; Diktas et al, 2021 ; El‐Boghdadly et al, 2020; Franklin & Gkiouleka, 2021 ; Veziant et al, 2020). Several well-documented risk factors faced by the medical staff in the workplace during COVID-19 include high workload, direct contact with infected individuals, facing a higher rate of moral dilemmas (e.g., taking decisions about life and death), limited collegial and managerial support, perceived helplessness due to lack of experience or equipment and prolonged separation from families ( Gohar et al, 2020 ; Fang et al, 2021 ; Shanafelt et al, 2020 ; Walton & Christian, 2020; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study on organizational resilience processes among HCWs in Switzerland in the first year of the pandemic found that the difficulties in implementing COVID guidelines and protection measures fell in the category of problematic situations associated with the development of new standards, that is, HCWs became used to new ways of working and developed new skills to perform effectively [ 45 ]. A retrospective study performed at Sisli Hamidiye Etfal Training and Research Hospital in Istanbul, Turkey, found that sharp injuries rates per 1000 healthcare workers decreased during the pandemic period, mainly due to the procurement of personal protective equipment and organizing well-designed training and awareness programs at the beginning and during the COVID-19 pandemic period, even if the possibility of underreporting may limit the significance of the results [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, congruently, they also had to contend with changes in their practices including retraining and redeployment to cope with the rapidly increasing number of positive COVID-19 cases ( 20 ). This is particularly true for frontline nurses who must adapt to the increased workloads, discomfort with extra layers of PPEs and greater risk of exposure to occupational hazards, including contact with contaminated instruments and patient secretions, contributing to higher anxiety not only for their own safety but that of their families ( 29 ).…”
Section: Discussionmentioning
confidence: 99%